A4_2 A Bright Night - Barker, Joshua; Coxon, John; Conlon, Thomas (Physics Special Topics, 2011)
The gas giant planet Jupiter is often referred to asa ‘failed star’. This paper investigates whether a change in brightness levels would be experienced by the Earth if Jupiter was in fact undergoing fusion and radiating. It is found that the luminosity generated by nuclear fusion within Jupiter would be a very small percentage of that produced by the Sun, even in the case where the mass of Jupiter is increased.